The Effectiveness of Mindfulness-Based Sex Therapy on Multidimensional Sexual Issues and Sexual Distress in Women with Urotophobia Disorder - Rahmani, Milad; Anasseri, Mehryar (Psychology of Woman Journal, 2023)
The purpose of this study was to determine the effectiveness of mindfulness-based sex therapy on multidimensional sexual issues and sexual distress in women with urotophobia disorder. The present study is a semi-experimental with a pretest-posttest design of two groups. The statistical population of this study was all women with urotophobia disorder in Tehran in 1402. In the present study, 18 women with urotophobia disorder were selected using purposive non-random sampling and then 9 women were selected randomly as control group and 9 others as experimental group and finally, 8 participants of each group successfully completed the treatment. The experimental group participated in 8 sessions of 120 minutes once a week (within 2 months) of mindfulness-based sex therapy while the control group did not receive any intervention. Multidimensional Sexuality and Sexual Distress Questionnaires were used. The collected data were analyzed using multivariate and univariate analysis of covariance. The results showed that there was a significant difference between the mean scores of the experimental and control groups and mindfulness-based sex therapy significantly improved multidimensional sexual issues and sexual distress. Based on the findings of this study, interventions based on this approach can be effective in improving multidimensional sexual issues, sexual security and sexual distress in women with urotophobia disorder.